Bioethanol production by a xylan fermenting thermophilic isolate Clostridium strain DBT-IOC-DC21. (June 2018) - Singh, Nisha; Puri, Munish; Tuli, Deepak K.; Gupta, Ravi P.; Barrow, Colin J.; Mathur, Anshu S.
Abstract: To overcome the challenges associated with combined bioprocessing of lignocellulosic biomass to biofuel, finding good organisms is essential. An ethanol producing bacteria DBT-IOC-DC21 was isolated from a compost site via preliminary enrichment culture on a pure hemicellulosic substrate and identified as a Clostridium strain by 16S rRNA analysis. This strain presented broad substrate spectrum with ethanol, acetate, lactate, and hydrogen as the primary metabolic end products. The optimum conditions for ethanol production were found to be an initial pH of 7.0, a temperature of 70 °C and an L-G ratio of 0.67. Strain presented preferential hemicellulose fermentation when compared to various substrates and maximum ethanol concentration of 26.61 mM and 43.63 mM was produced from xylan and xylose, respectively. During the fermentation of varying concentration of xylan, a substantial amount of ethanol ranging from 25.27 mM to 67.29 mM was produced. An increased ethanol concentration of 40.22 mM was produced from a mixture of cellulose and xylan, with a significant effect observed on metabolic flux distribution. The optimum conditions were used to produce ethanol from 28 g L −1 rice straw biomass (RSB) (equivalent to 5.7 g L −1 of the xylose equivalents) in which 19.48 mM ethanol production was achieved. Thus, Clostridium strain DBT-IOC-DC21 has the potential to perform direct microbial conversion of untreated RSB to ethanol at a yield comparative to xylan fermentation. Highlights: Hemicellulose-fermenting thermophilic anaerobic bacteria isolate from compost. Broad substrate spectrum. High ethanol yield from glucose, cellobiose, xylose, and arabinose. Maximum 67.29 mM ethanol produced from high concentration (25 g L-1) of xylan. Direct microbial conversion of untreated rice straw biomass.